Surface Modification of Biomaterials: A Quest for Blood Compatibility - Achala de Mel; Brian G. Cousins; Alexander M. Seifalian (International Journal of Biomaterials)
Cardiovascular implants must resist thrombosis and intimal hyperplasia to maintain patency. These implants when in contact with blood face a challenge to oppose the natural coagulation process that becomes activated. Surface protein adsorption and their relevant 3D confirmation greatly determine the degree of blood compatibility. A great deal of research efforts are attributed towards realising such a surface, which comprise of a range of methods on surface modification. Surface modification methods can be broadly categorized as physicochemical modifications and biological modifications. These modifications aim to modulate platelet responses directly through modulation of thrombogenic proteins or by inducing antithrombogenic biomolecules that can be biofunctionalised onto surfaces or through inducing an active endothelium. Nanotechnology is recognising a great role in such surface modification of cardiovascular implants through biofunctionalisation of polymers and peptides in nanocomposites and through nanofabrication of polymers which will pave the way for finding a closer blood match through haemostasis when developing cardiovascular implants with a greater degree of patency.